Los incrementos de la remuneración mínima vital y el nivel de empleo en las macrorregiones del Perú entre los años 2015 y 2022 - Perez Figueredo, Nohelia Patricia (2025)
This research expands academic knowledge on the relationship between the minimum living wage (RMV) in the labor market and employment levels. By examining the dependence between increases in the RMV and both formal employment and the presence of a second job, a new perspective is opened for understanding the complexity of wage policymaking in the labor market. The results obtained from the hypothesis testing allow us to maintain that increases in the RMV, although normatively relevant, have not had a significant impact on employment levels or the reduction of multiple employment in the macroregions of Peru. This finding is consistent with reports in the international and national literature and raises the need to review the RMV not as an isolated tool, but as part of a broader set of labor and production policies aimed at addressing informality, increasing productivity, and ensuring sustainable incomes for workers.